(untitled) (International Journal of Engineering and Computer Science, 2017)
Subsurface parameter characterization for ground penetrating radar (GPR) is very challenging given the typically lossy, cluttered soil with varying conditions form one environment to another. An approximation of the velocity of propagation for homogeneous, isotropic, non-magnetic materials is used to aid the evaluation of GPR measurements and subsurface parameter estimation. For landmine detection, parameter estimation introduces increased complexity due to soil heterogeneity and clutter signals. This paper presents the results of a study that investigates the relationship between the velocity of propagation with soil and mine parameters for a landmine detection application using GPR. Most GPR studies for landmine detection focus on vehicular systems or scanned measurements. This study assumes a homogeneous, non-magnetic soil for a handheld impulse GPR system based on A-scan data. Synthetic data is used to undertake empirical experiments, performed in the CST STUDIO SUITE environment for 3D electromagnetic analysis.